ACETAMINOPHEN EFFECT ON FREE RADICAL OXIDATION INDICES IN RATS WITH TYPE 2 DIABETES MELLITUS - Furka, O. B.; Ivanusa, I. B.; Mykhalkiv, M. M.; Klishch, I. M. (International Journal of Medicine and Medical Research, 2017)
Background. Acetaminophen is a drug used to relieve pain syndrome. It is used both independently and in composition of combined drugs. Type 2 diabetes is an age-related disease that is associated with a violation of insulin synthesis by pancreas. Objective. The aim of the research was to study the effect of acetaminophen on major free radical oxidation indices of rats with type 2 diabetes mellitus in time dynamics. Methods. We conducted two series of experiments. The first series comprised rats with type 2 diabetes mellitus and acute acetaminophen toxic lesions. The second series involved rats with type 2 diabetes mellitus and acetaminophen administration at a dose of 55 mg/kg for the period of 7 days. Results. Administration of acetaminophen for rats with type 2 diabetes mellitus caused the increase in the content of malondialdehyde, diene and triene conjugates and Schiff bases in blood plasma and malondialdehyde, diene and triene conjugates in liver homogenate. The maximum increase in these indices was observed on the first day of the experiment. Gradually these indices decreased on the 3rd, 5th and 7th days of the experiment. Conclusions. Free radical oxidation increased in both series of the experiment. This process developed in rats with type 2 diabetes mellitus and acute acetaminophen toxic lesions more intensively, than in rats with type 2 diabetes mellitus and administration of acetaminophen at the highest therapeutic dose during 7 days.